Health promoting spirulina platensis nanoparticles induce early embryonic loss in heat-stressed rabbit does - Emtenan M. Hanafi; Ismail A. Elnady; Mohamed I. Shehab El-Din; Yasser H. A. Saber; Manal M. Ramadan; Reda M. S. Korany; Ghada H. Elsayed (Scientific Reports, 2026)
Abstract Heat stress poses a major constraint to rabbit production by impairing reproductive performance, compromising embryo survival, and increasing oxidative stress. Spirulina, known for its rich content of proteins, antioxidants, and bioactive compounds, has been proposed as a natural dietary supplement to mitigate these detrimental effects. The present study aimed to prepare nano size spirulina to evaluate its impact on reproductive performance and embryo survival of New Zealand White rabbit does under heat stress conditions. Sixty healthy pluriparous does were allocated into four groups: control (G1), heat stress (G2), and two heat-stressed groups (G3 and G4) supplemented with spirulina nanoparticles at two different levels. Reproductive traits, hormonal profiles, oxidative stress markers, proinflammatory cytokines and histopathological changes were assessed. The results revealed that heat stress significantly reduced fertility rates, progesterone levels, and increased embryonic loss, accompanied by oxidative damage and inflammatory responses. Supplementation with spirulina nanoparticles improved the general health condition of mothers and alleviated the adverse effects of heat stress; elevated antioxidant capacity, number of oocytes, conception and implantation. However, spirulina nanoparticle supplementation also exerted immunomodulatory effects that were associated with inadequate development of the placental spiral arteries and increased early embryonic loss in the treated groups. These findings suggest that spirulina nanoparticles may offer protective benefits against heat stress in rabbits, but caution was advised regarding using nanoparticles for does kept for breeding.